Balance between surgical and therapeutic treatment of chronic pancreatitis is a fundamental factor of functional outcome and quality of life of patients - V. N. Klymenko; A. V. Klymenko; A. A. Steshenko (Zaporožskij Medicinskij Žurnal)
Relevance. The progressive course of CP with ductal hypertension causes severe pain, exo-, endocrine failure, reduces the quality of life and requires surgical treatment.